RUNX-2, OPN and OCN expression induced by grey and white mineral trioxide aggregate in normal and hypertensive rats - Martins, C. M.; Azevedo Queiroz, I. O. de [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Gomes Filho, João Eduardo [UNESP] (Wiley-Blackwell, 2018)
AimTo investigate whether hypertension affects mineralization associated with white and grey mineral trioxide aggregate (MTA Angelus((R))) implanted subcutaneously into rats by assaying osteoblastic biomarkers. MethodologyPolyethylene tubes containing grey MTA Angelus((R)), white MTA Angelus((R)), intermediate restorative material (IRM; positive control) or an empty tube (negative control) were implanted into the dorsal connective tissue of spontaneous hypertensive (n=12) and Wistar (normotensive; n=10) rats. Half of the rats in each group were killed after 7days, and the remaining after 30days. Tubes with surrounding tissue were removed, and immunostaining was performed to detect RUNX-2, OPN and OCN proteins. The normality of data was analysed using the Shapiro-Wilk test. Comparison of two independent groups was performed using the Mann-Whitney U-test, to detect a significant difference. A post hoc test accounting for multiple comparisons was performed following Tukey's test (P<0.05). ResultsUnder hypertensive conditions after 30days, both MTA materials were associated with immunolabelling for RUNX-2 from low to moderate, which was less than that observed at normal blood pressure and the 7-day groups (P<0.05). The expression of OPN and OCN proteins under both MTA conditions was considered low after both 7 and 30days for the hypertensive condition, and was less than that in animals with normal blood pressure after 30days (P<0.05). No immunostaining for any biomarkers in the control and IRM groups was observed (P<0.05). ConclusionHypertension decreased the immunostaining of RUNX-2, OPN and OCN biomarkers in response to MTA. Thus, hypertension can jeopardize the mineralization ability of MTA and may have a negative impact on endodontic treatment outcomes.
Keywords: calcification; hypertension; mineral trioxide aggregate; periapical diseases